Political economy of citizenship regimes: Tax in India and Brazil - Aaron Schneider (United Nations Research Institute for Social Development (UNRISD), 2015)
Patterns of change in citizenship regimes help explain differences in tax structure in Brazil and India. Changes to citizenship regimes include the mobilization of new collective identities, the substantive demands they articulate, and the stable linkages that connect them to public life. When excluded groups mobilize and gain access to citizenship regimes, they provide new sources of legitimacy to states, which can call on sacrifice from a broader range of social actors and thereby increase state capacity, for example in tax. Changes to tax can be evaluated in terms of levels of revenues, degrees of progressivity, and the universality of application of tax across sectors and regions. Since the 1970s in Brazil and India, excluded groups constituted new collective identities, articulated demands of the state, and secured stable linkages connecting state and society. These processes deepened democracy in both countries, but there were differences in the types of collective identities mobilized, the demands articulated, and the mechanisms of linkage between state and society. In Brazil, a cross-class coalition of previously excluded working class, social movement, and middle class actors provided a social base that mobilized in the struggle for democratization and articulated demands in opposition to neoliberal stabilization during the 1990s. When growth returned in the 2000s, they were provided stable linkages to the state through social policies and institutions that made use of expanded revenues. Despite a cross-class coalition stably linked to the state through policies and institutions, particularities of Brazilian politics force the accommodation of economic and political elites, and they have blocked more significant efforts to reverse patterns of inequity in the tax system that appear both in terms of regressivity and a lack of universality. In India, a variety of middle class, caste, regional, and identity-based interests struggled for access to the polity and displaced Congress dominance. In the context of elite consensus around neoliberal stabilization, these previously excluded groups framed their demands around recognition and benefits targeted to identity-based groups, with patterns of linkage to the state through cycling combinations of regionally-specific alliances producing a patchwork of policies, institutions, and legislation linking to the state. This pattern of competitive coalition-building has failed to generate cross-class support for increased revenues, and has exacerbated the lack of progressivity and universality in tax. The lessons of this study shed light on the role of cross-class coalitions in supporting state capacity in the form of increased revenues. At the same time, they reveal that the formation of cross-class coalitions is a highly contingent process, depending on the political, economic, and cultural determinants of changes to citizenship regimes, in which previously excluded groups mobilize and pursue mechanisms of incorporation to the polity.
Keywords: 330